Association of ABO blood group with CAD in patients undergoing CAG in Cardiology Department of Dhaka Medical College and Hospital - Hasan, Md Nazmul; Chowdhury, Abdul Wadud; Islam, Lahani Md Tajul; Safiuddin, Mohammad; Haque, Mostashirul; Hoque, Harisul (University Heart Journal, 2015)
There are many reports regarding association between ABO and Rhesus blood groups and coronary artery disease. This study has been designed to see the association of ABO blood group with coronary artery disease in patient who were admitted in Cardiology Department of Dhaka Medical College and Hospital and undergoing coronary angiography. A total of 680 patients were studied in this retrospective study. ABO blood group, gender and standard cardiovascular risk factors were determined. In our study 17.5% of the study population were female with mean age of 49.94±10.37 years and 82.5% were male with a mean age 49.68±10.45 years . Most of the patients belonged to blood group B (33.4%) .Our results demonstrated the prevalence of CAD in blood group B is much higher than other blood groups which is in contrast with other studies in few other countries including one study done on small groups of people in Bangladesh. Geographical distribution may explain the variation in results among countries. University Heart Journal Vol. 10, No. 2, July 2014; 81-84